Predictors of 30-day mortality among patients with stroke admitted at a tertiary teaching hospital in Northwestern Tanzania: A prospective cohort study - Matuja, Sarah Shali; Mlay, Gilbert; Kalokola, Fredrick; Ngoya, Patrick; Shindika, Jemima; Andrew, Lilian; Ngimbwa, Joshua; Ahmed, Rashid Ali; Tumaini, Basil; Khanbhai, Khuzeima; Mutagaywa, Reuben; Manji, Mohamed; et al. (Frontiers in Neurology, 2023)
Background Stroke is the second leading cause of death worldwide, with the highest mortality rates in low- to middle-income countries, particularly in sub-Saharan Africa. We aimed to investigate the predictors of 30-day mortality among patients with stroke admitted at a tertiary teaching hospital in Northwestern Tanzania. Methods This cohort study recruited patients with the World Health Organization's clinical definition of stroke. Data were collected on baseline characteristics, the degree of neurological impairment at admission (measured using the National Institutes of Health Stroke Scale), imaging and electrocardiogram (ECG) findings, and post-stroke complications. The modified Rankin scale (mRS) was used to assess stroke outcomes. Kaplan–Meier analysis was used to describe survival, and the Cox proportional hazards model was used to examine predictors of mortality. Results A total of 135 patients were enrolled, with a mean age of 64.5 years. Hypertension was observed in 76%, and 20% were on regular anti-hypertensive medications. The overall 30-day mortality rate was 37%. Comparing patients with hemorrhagic and ischemic stroke, 25% had died by day 5 [25th percentile survival time (in days): 5 (95% CI: 2–14)] versus day 23 [25th percentile survival time (in days): 23 (95% CI: 11–30) (log-rank p < 0.001)], respectively. Aspiration pneumonia was the most common medical complication, occurring in 41.3% of patients. ECG abnormalities were observed in 54.6 and 46.9% of patients with hemorrhagic and ischemic stroke, respectively. The most common patterns were as follows: ST changes 29.6 vs. 30.9%, T-wave inversion 34.1 vs. 38.3%, and U-waves 18.2 vs. 1.2% in hemorrhagic and ischemic stroke, respectively. Independent predictors for case mortality were as follows: mRS score at presentation (4–5) [aHR 5.50 (95% CI: 2.02–15.04)], aspiration pneumonia [aHR 3.69 (95% CI: 1.71–13.69)], ECG abnormalities [aHR 2.28 (95% CI: 1.86–5.86)], and baseline stroke severity [aHR 1.09 (95% CI: 1.02–1.17)]. Conclusion Stroke is associated with a high 30-day mortality rate in Northwestern Tanzania. Concerted efforts are warranted in managing patients with stroke, with particular attention to individuals with severe strokes, ECG abnormalities, and swallowing difficulties to reduce early morbidity and mortality.